(untitled) (Research, Society and Development, 2021)
The present study analyzed a set of prescriptions in two adult intensive care units in a public hospital in northern Brazil. A cross-sectional, quantitative, documentary and descriptive research was carried out, considering 270 shape prescriptions. The analysis was performed by a qualified pharmacist, using a questionnaire with seventeen assertive questions as an instrument for data collection. This research was carried out in adult intensive care units with a total of eighteen beds in the period from April 1st to 15th, 2021. In this research, divergences in the indicators were identified: patient weight, medical record number, dosage, schedule, Denomination Common Brazilian, form of dilution, infusion rate and use of the expression if necessary. Prescription errors have become common nowadays, being evidenced as a risk to the health and life of patients. Considering the divergence index in prescriptions, it is necessary for the pharmacist to work in an integral way for the analysis of prescriptions and pharmaceutical interventions, thus seeking to ensure a better pharmacotherapy for patients.